The Revival of an Old Narrative to Counter Terrorism: The “Balkh School Approach” to Neutralizing the Neo-Kharijite Narrative in the Islamic World - Mirwais Balkhi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
The purpose of this article is to explain why, despite numerous collective and individual efforts, states have failed to eradicate terrorism produced by Islamic extremism. What alternatives to present paradigms possibly exist in the battle against terrorism and extremism? Through its neo-Kharijite and takfiri character, the irreconcilable extremism that developed at the end of the Cold War due to a leadership vacuum in the Islamic world, has caused widespread unease among Muslims and others. As a result, the current study approaches the topic of countering extremism from an entirely new perspective, which is nearly unprecedented in the literature. Because the current ways of combating extremism are either war or spreading alternate narratives. However, this piece resurrects a historic practice of weakening extremism. The revival of the Balkh school as an existent and viable alternative narrative in the Islamic world might diminish extremist and takfiri discourses. The Balkh school is a good opportunity to revive a peaceful tradition among Muslims in order to end extremism. A good and better way is to update and expand successful and effective narratives of the past that have shown significant achievements in the field of moderation and reciprocity with the use of modern tools.